Jejak Kanunisasi dalam Fikih Islam - Muhammad Ikhsan (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2018)
This research analyzes one of manifestation on Fiqh norms of Islam in the form of canonization or Taqnin. Subjects discussed in this research is (1) the Islamic Juristperspectives, (2) brief history of canonization in the history Islamic Jurisprudence. (3) The study of canonization in the al-Fatwa al-Hindiyah, one of the book discussing on Islamic Jurisprudence in the era of Sultan Aurungzeb in Anak Benua region, India during the 17th century. This research applied literary review which analyzes the book of al-Fatawa al-Hindiyah.